2010
DOI: 10.3892/etm_00000031
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid capture II for high-risk human papillomavirus DNA testing to detect cervical precancerous lesions: A qualitative and quantitative study

Abstract: Hybrid capture Ⅱ (HC-Ⅱ) is the only technique that can be used in clinical human papillomavirus (HPV) DNA detection. However, there is controversy in regards to how to analyze and assess the viral load of high-risk (HR)-HPV by use of HC-Ⅱ and the relation between viral load and cervical lesions. In this study, we analyzed the results of a sequential screening of outpatients at the Department of Obstetrics and Gynecology of the China-Japan Friendship Hospital, and we aimed to explore the relationship between HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Koilocytosis, bi-nucleation and dyskeratosis were observed in intraepithelial neoplasias of the cervix at relatively the following frequency of 92.24 and 46% in this study. During the study on the quantitative and qualitative detection of Papillomavirus in precancerous lesions of the cervix, the authors observed koilocytosis in a frequency of 61.2% of intraepithelial neoplasms of the cervix [61]. In a study looking for papillomavirus infection in women from Lubumbashi, the authors found the presence of koilocytosis in 92.7% of cases of intraepithelial neoplasia.…”
Section: Cytological Alterations Predictive Of Papillomavirus Infectionmentioning
confidence: 99%
“…Koilocytosis, bi-nucleation and dyskeratosis were observed in intraepithelial neoplasias of the cervix at relatively the following frequency of 92.24 and 46% in this study. During the study on the quantitative and qualitative detection of Papillomavirus in precancerous lesions of the cervix, the authors observed koilocytosis in a frequency of 61.2% of intraepithelial neoplasms of the cervix [61]. In a study looking for papillomavirus infection in women from Lubumbashi, the authors found the presence of koilocytosis in 92.7% of cases of intraepithelial neoplasia.…”
Section: Cytological Alterations Predictive Of Papillomavirus Infectionmentioning
confidence: 99%
“…Total of 38 studies were excluded with reasons -22 studies were clearly excluded as articles did not fulfill the inclusion criteria for study settings. 16 studies from LMICs were excluded with reasons: Studies reported test characteristic of HC2 on hospital based data (Sodhani et al, 2006;Ma et al, 2010;Bhatla et al, 2012), study had no clarity on type of settings (Katyal et al,2011), studies reported estimates of HC2 on CIN3+ lesion only (Moy et al, 2010;Belinson et al, 2011;Nieves et al, 2013), studies mentioned no estimates of test characteristics of HC2 test or CI intervals (Schiffman et al, 2000;Sankaranarayanan et al, 2009;Cagle et al, 2010;Li et al, 2010;Girianelli et al, 2006), duplicate data, cytology as gold standard (Belinson et al, 2001;Blumenthal et al, 2001;Longatto-Filho et al, 2012;Katanga et al, 2019). Total 18 population based cross-sectional studies fulfilling the eligibility criteria were included in the analysis.…”
Section: Data Sources and Searchesmentioning
confidence: 99%